Adduction of ammonium to polylactides to modify their dissociation behavior in collision‐induced dissociation. (31st January 2018) - Chendo, Christophe; Phan, Trang N.T.; Rollet, Marion; Gigmes, Didier; Charles, Laurence
Abstract : Rationale: The goal of this work was to modify the dissociation pathways of polylactide (PLA) holding benzyl and hydroxyl terminations, in order to circumvent coincidence of product ions generated during collisional activation of sodiated chains, which prevented their reliable characterization. Methods: Benzyl‐, hydroxyl‐terminated PLAs were ionized as ammonium adducts in positive ion mode electrospray and subjected to collision‐induced dissociation (CID). Tandem mass spectrometry (MS/MS) experiments were conducted in a quadrupole time‐of‐flight (QTOF) instrument for safe assignment of product ions based on their elemental composition derived from accurate mass measurements. Results: Adduction of ammonium to PLAs was found to induce chain fragmentation via charge‐assisted processes, in great contrast to the charge‐remote mechanisms experienced by sodiated molecules. The main reaction produced ions containing the ω termination only, hence allowing straightforward end‐group determination. Other minor pathways were studied in detail to establish dissociation rules for ammoniated PLAs. Some reactions were found to be end‐group specific, highlighting the higher reactivity of ammonium than alkali ion adducts. Conclusions: Changing the usually employed sodium‐cationizing agent to ammonium was shown to induce dramatic changes in the CID behavior of PLAs. This was a simple and efficient approach to address issues encountered for end‐group analysis of the particular PLA studied here.